Convergence or Divergence: Comparative Analysis of Sustainable Development Goals (SDGs) and Islamic Economic Principle - Yusuf, Jamiu Adeniyi; Araoye, Sikiru Okunlade; Ayuba , Ismail Aderole; Oladapo, Rauf Mumini; Tunde , Muhammed Azeem; Bolaji, Akinola Abdulbaaki (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study investigates the convergence and divergence between the Sustainable Development Goals (SDGs) and Islamic economic principles, with a focus on their shared priorities and areas of tension. The primary objective is to analyze how the ethical and operational frameworks of Islamic economics align with the global SDG agenda, particularly in the domains of poverty alleviation, environmental sustainability, and social justice. A case study methodology was employed, incorporating qualitative thematic analysis using NVivo software alongside theoretical comparative analysis to provide a comprehensive perspective. The findings reveal substantial alignment in ethical foundations, exemplified by the emphasis on equitable wealth distribution through instruments such as zakat and waqf, which correspond to SDG Goal 1 (No Poverty) and Goal 10 (Reduced Inequalities). However, notable divergences emerge, particularly regarding gender equality (Goal 5) and environmental governance frameworks (Goal 13). Key challenges identified include regulatory constraints, varying cultural interpretations, and a lack of empirical data on the impact of Islamic finance in advancing SDG targets. The study concludes that while Islamic economic principles offer significant potential for supporting SDG implementation, their scalability and effectiveness require strategic partnerships, contextual adaptation, and the development of robust data frameworks. Policy recommendations include fostering interfaith and policy dialogues, strengthening institutional capacities, and integrating Islamic financial instruments into national development strategies.